Application of Business Ethics and Business Law on Economic Democracy that Impacts Business Sustainability - M. Rizky Mahaputra; Farhan Saputra (Dinasti Research, 2021)
Ethics and Business Law are identical to the rules and procedures for running our business by existing laws not to harm any party. An excellent economic activity, of course, has complied with the regulations that have been set. The implementation of an affair, trade, industry or related financial activity carried out by a business entrepreneur. Business Law can determine the progress of a company or other entrepreneur in implementing their performance because every company has different principles. Of course, every country also has different business laws. As an increasingly developed country, Indonesia is expected to be able to implement business law enforcement evenly.